Vision quest [videorecording (Blu-Ray)] - Ponicsan, Darryl; Modine, Matthew; Fiorentino, Linda; Schoeffling, Michael; Davis, Terry (Archive collection., 2017)
Matthew Modine stars as a high school wrestler trying to shed 23 pounds in a dangerously short time and take on the undefeated, tough as nails 168-pound champion.